Emotion components and social relations - Parkinson, B (Taylor and Francis (Routledge), 2017)
The history of classic emotion theories can be seen as a series of attempts to identify the specific causal process that generates the phenomenon in question: the “goose which lays the golden eggs” in James’ (1898, p. 449) terms. Moors’ (this issue) integrative target article combines insights from both classic and skeptical theorists. Her conclusion is that emotion is not a golden egg, but that goose-hunting is not wildly misguided, because it may lead researchers to causal mechanisms that can account for processes conventionally associated with emotion, and for associations between these supposed emotion components. This commentary focuses on two aspects of Moors’ analysis. First, I consider her positive proposals about the role of appraisals and goal-directed mechanisms in the causation of emotion-related behaviour, and argue that these processes are more fully understood in their broader temporal and social context. Attention to the functional properties of emotional behavior from this wider perspective may reveal an underlying coherence that is less apparent at the molecular level. Next, I turn to the skeptical aspect of Moors’ proposal, and argue that vernacular emotion concepts may play constitutive roles in the perception, experience, and regulation of emotional activity. These representation-dependent processes extend the range of possible ways in which emotions can function to align relations between people and events in the shared environment, and add another layer of meaningful structure to emotional processes.